Keterikatan Kerja dan Intensi Turnover pada Karyawan Generasi Y - Dewi, Gusti Ayu Made Dwi Aprillia; Savira, Alice Whita (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2022)
This research aimed to determine the correlation between work engagement with turnover intention among generation Y employees. The research hypothesis proposed that there was a negative correlation between work engagement with turnover intention among generation y employees. The participants in this study were 411 generation Y employees. This research was a quantitative study with non-probability sampling technique. The data was collected by distributing online scales which are Utrecht Work Engagement Scale-9 (UWES-9) and Turnover Intention Scale Six Items (TIS-6). From the try-out of scales, the reliability of coefficients on UWES-9 was .91 and TIS-6 was .78. The data was analyzed using Pearson Product Moment Correlation technique because the data was normally distributed. The result of the analysis test showed that work engagement has a negative correlation with turnover intention with r = -.63; p .01. Based on the result, it can be concluded that there was a significant negative correlation between work engagement with turnover intention among generation y employees.